INVESTMENT-BASED INSURANCE DISPUTE PREVENTION (UNITLINK) IN INDONESIA - Fauzi, Wetria (Universitas Ekasakti, 2023)
Investment-based insurance (unitlink) is a hybrid product from insurance companies that is very vulnerable to causing disputes. Innovations in the development of unit-linked investment-based insurance products continue to cause constant polemics, many policyholders are disadvantaged. What efforts can be made in order to prevent the occurrence of such disputes. This research was carried out using a normative juridical method using a statutory and conceptual approach. Prevention of unitlink insurance disputes is to apply the principle of perfect honesty (Utmost good faith) for both policyholders and insurance agents. and improve the supervisory function of the Financial Services Authority (OJK) in accordance with existing regulations. Integrated supervision for all financial institutions in accordance with unitlink insurance which is a hybrid product of insurance and investment. Coordination between insurance company associations and OJK needs to be improved, so that supervision of insurance companies, in this case insurance agents can be carried out optimally, so as to prevent unit-linked insurance disputes.